Getting Down to Business: Chain Ownership and Fertility Clinic Performance - La Forgia, Ambar; Bodner, Julia (Management Science, 2025)
Acquisitions by corporate entities have fueled the growth of chain organizations in healthcare. A chain is a multiunit firm under the same ownership and management providing similar services in different locations. Chain ownership has been credited with boosting firm performance in the retail and service sectors but has been criticized for prioritizing profits over the well-being of patients in the healthcare sector. This paper finds that chain ownership improves healthcare outcomes in the market for in vitro fertilization (IVF). Using novel data on U.S. fertility clinics and difference-in-differences methods, we find that IVF cycles increase by 27.2%, and IVF success rates increase by 13.6% after acquisition by a fertility chain. We provide evidence that fertility chains facilitate resource and knowledge transfers needed to enhance quality and expand the IVF market. For example, acquired clinics change IVF processes and procedures to achieve the IVF gold standard of simultaneously reducing higher-risk multiple births and increasing singleton births. We discuss how the fertility sector’s relatively minimal market frictions and information asymmetries may incentivize chain owners to invest in quality. This paper was accepted by Stefan Scholtes, healthcare management. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.02793 .